Imaging leukocyte trafficking in vivo with two-photon-excited endogenous tryptophan fluorescence - Li, Chunqiang; Pastila, Riikka K.; Pitsillides, Costas (My University, 2010)
We describe a new method for imaging leukocytes in vivo by exciting the endogenous protein fluorescence in the ultraviolet (UV) spectral region where tryptophan is the major fluorophore. Two-photon excitation near 590 nm allows noninvasive optical sectioning through the epidermal cell layers into the dermis of mouse skin, where leukocytes can be observed by video-rate microscopy to interact dynamically with the dermal vascular endothelium. Inflammation significantly enhances leukocyte rolling, adhesion, and tissue infiltration. After exiting the vasculature, leukocytes continue to move actively in tissue as observed by time-lapse microscopy, and are distinguishable from resident autofluorescent cells that are not motile. Because the new method alleviates the need to introduce exogenous labels, it is potentially applicable for tracking leukocytes and monitoring inflammatory cellular reactions in humans
Keywords: Harmonic generation; Collagen; Generation microscopy